Impact of dienogest pretreatment on IVF-ET outcomes in patients with endometriosis: a systematic review and meta-analysis - Wenjing Shao; Yuying Li; Yanli Wang (BMC, 2023)
Abstract Background To comprehensively evaluate the influence of dienogest (DNG) versus non-DNG pretreatment on in vitro fertilization and embryo transfer (IVF-ET) outcomes for patients with endometriosis. Methods PubMed, Embase, Cochrane Library, Web of Science, CNKI, WanFang, and VIP were comprehensively searched for relevant publications until September 14, 2022. Primary outcomes included clinical pregnancy rate and live birth rate. Secondary outcomes included retrieved oocytes, mature oocytes, blastocysts, growing follicles, transferrable embryos, fertilization rate, implantation rate, and miscarriage rate. Subgroup analysis was performed according to different grouping methods and embryo types. Results Five studies of 568 females with endometriosis were involved in this systematic review and meta-analysis. DNG treatment exhibited similar effects to non-DNG treatment on either the primary or the secondary outcomes (all P > 0.05). The DNG group had a significantly greater clinical pregnancy rate than the non-hormonal treatment group (pooled relative risk [RR]: 2.055, 95% confidence interval [CI]: 1.275, 3.312, P = 0.003), and exhibited a significantly lower clinical pregnancy rate than the long gonadotropin-releasing hormone agonist (GnRH-a) group (RR: 0.542, 95%CI: 0.321, 0.916, P = 0.022). For patients undergoing fresh embryo transfer, the DNG group displayed a significantly greater clinical pregnancy rate versus the non-DNG group (pooled RR: 1.848, 95%CI: 1.234, 2.767, P = 0.003). Patients receiving DNG had a significantly greater live birth rate than those with non-hormonal treatment (pooled RR: 2.136, 95%CI: 1.223, 3.734, P = 0.008), while having a significantly lower live birth rate than the long GnRH-a group (RR: 0.441, 95%CI: 0.214, 0.907, P = 0.026). While using fresh embryos, patients with DNG treatment had an increased live birth rate, compared with those without DNG treatment (pooled RR: 2.132, 95%CI: 1.090, 4.169, P = 0.027). Conclusion DNG treatment may have similar effects to non-DNG treatment on IVF-ET outcomes. The clinical pregnancy rate and live birth rate after DNG treatment may be significantly higher than those after non-hormonal treatment. More evidence is warranted to corroborate these findings.